Brief Report: AIDS-Defining Events and Deaths in HIV-Infected Children and Adolescents on Antiretrovirals. (1st January 2018) - Traisathit, Patrinee; Delory, Tristan; Ngo-Giang-Huong, Nicole; Somsamai, Rosalin; Techakunakorn, Pornchai; Theansavettrakul, Sookchai; Kanjanavanit, Suparat; Mekmullica, Jutarat; Ngampiyaskul, Chaiwat; Na-Rajsima, Sathaporn; Lallemant, Marc; Cressey, Tim R.; et al.
Abstract : Background: Data are scarce on the long-term clinical outcomes of perinatally HIV-infected children and adolescents receiving antiretroviral therapy (ART) in low/middle-income countries. We assessed the incidence of mortality before (early) and after (late) 6 months of ART and of the composite outcome of new/recurrent AIDS-defining event or death >6 months after ART start (late AIDS/death) and their associated factors. Methods: Study population was perinatally HIV-infected children (⩽18 years) initiating ART within the Program for HIV Prevention and Treatment observational cohort (NCT00433030). Factors associated with late AIDS/death were assessed using competing risk regression models accounting for lost to-follow-up and included baseline and time-updated variables. Results: Among 619 children, "early" mortality incidence was 99 deaths per 1000 person-years of follow-up [95% confidence interval (CI): 69 to 142] and "late" mortality 6 per 1000 person-years of follow-up (95% CI: 4 to 9). Of the 553 children alive >6 months after ART initiation, median age at ART initiation was 6.4 years, CD4% 8.2%, and HIV-RNA load 5.1 log10 copies/mL. Thirty-eight (7%) children developed late AIDS/death after median time of 3.3 years: 24 died and 24 experienced new/recurrent AIDS-defining events (10 subsequently died). Factors independently associated with late AIDS/death were current age ≥13 years (adjusted subdistribution hazard ratio 4.9; 95% CI: 2.4 to 10.1), HIV-RNA load always ≥400 copies/mL (12.3; 95% CI: 4.0 to 37.6), BMI-z-score always <−2 SD (13.7; 95% CI: 3.4 to 55.7), and hemoglobin <8 g/dL at least once (4.6; 95% CI: 2.0 to 10.5). Conclusions: After the initial 6 months of ART, being an adolescent, persistent viremia, poor nutritional status, and severe anemia were associated with poor clinical outcomes. This supports the need for novel interventions that target children, particularly adolescents with poor growth and uncontrolled viremia.